Step 1

Given: \(\displaystyle{8}-{\frac{{{5}}}{{{x}}}}={2}+{\frac{{{3}}}{{{x}}}}\)

To solve- The above equation.

Step 2

Explanation- Rewrite the given expression,

\(\displaystyle{8}-{\frac{{{5}}}{{{x}}}}={2}+{\frac{{{3}}}{{{x}}}}\)

Simplifying the above expression transfering the x-term from right hand side to left hand side and constant term from left hand side to right hand side, we get,

\(\displaystyle-{\frac{{{3}}}{{{x}}}}-{\frac{{{5}}}{{{x}}}}={2}-{8}\)

\(\displaystyle{\frac{{-{3}-{5}}}{{{x}}}}=-{6}\)

\(\displaystyle{\frac{{-{8}}}{{{x}}}}=-{6}\)

Further simplify the above expression, we get,

\(\displaystyle{x}={\frac{{-{8}}}{{-{6}}}}\)

\(\displaystyle{x}={\frac{{{4}}}{{{3}}}}\)

Answer- Hence, the solution of the expression \(\displaystyle{8}-{\frac{{{5}}}{{{x}}}}={2}+{\frac{{{3}}}{{{x}}}}\ {i}{s}\ {x}={\frac{{{4}}}{{{3}}}}\).

Given: \(\displaystyle{8}-{\frac{{{5}}}{{{x}}}}={2}+{\frac{{{3}}}{{{x}}}}\)

To solve- The above equation.

Step 2

Explanation- Rewrite the given expression,

\(\displaystyle{8}-{\frac{{{5}}}{{{x}}}}={2}+{\frac{{{3}}}{{{x}}}}\)

Simplifying the above expression transfering the x-term from right hand side to left hand side and constant term from left hand side to right hand side, we get,

\(\displaystyle-{\frac{{{3}}}{{{x}}}}-{\frac{{{5}}}{{{x}}}}={2}-{8}\)

\(\displaystyle{\frac{{-{3}-{5}}}{{{x}}}}=-{6}\)

\(\displaystyle{\frac{{-{8}}}{{{x}}}}=-{6}\)

Further simplify the above expression, we get,

\(\displaystyle{x}={\frac{{-{8}}}{{-{6}}}}\)

\(\displaystyle{x}={\frac{{{4}}}{{{3}}}}\)

Answer- Hence, the solution of the expression \(\displaystyle{8}-{\frac{{{5}}}{{{x}}}}={2}+{\frac{{{3}}}{{{x}}}}\ {i}{s}\ {x}={\frac{{{4}}}{{{3}}}}\).